ЗНАЧЕНИЕ РУССКОГО СЛОВА В АСПЕКТЕ ПЕРЕВОДА - Разумовская, Вероника (Studia Rossica Posnaniensia, 2008)
The paper deals with the problem of poetic translation. The discussion is based on several universal linguistic and translation categories: meaning, sense, expression, form and the unit of translation. The semantic and cultural peculiarities of Russian words in the novel Eugene Onegin in the aspect of translation are described.